2002
DOI: 10.2307/2694567
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Dating of Faunal Materials by Ion-Selective Electrode: High Resolution Relative Dating at an Early Agricultural Period Site in the Tucson Basin

Abstract: When the fluoride content of bone is measured with an ion-selective electrode, and when the technique is correctly applied, fluoride dating is a very economical method for developing fine-scale relative chronologies. It has been successfully used to develop relative chronologies for prehistoric human burials and fossilized bones throughout the world, but its much greater potential for the dating of unfossilized faunal materials has been neglected. The fluoride contents of 889 lagomorph and 16 artiodactyl bones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In addition, the fact that no significant differences were observed in the prevalence or frequency of caries or AMTL between temporal phases at La Playa suggests that dietary composition remained stable over the entire course of the Early Agricultural period. This is supported by the botanical evidence from sites in southern Arizona that demonstrate an overall increase in resource consumption, but not an increased reliance on domesticated cultigens (Adams, 1998;Schurr & Gregory, 2002). The conjunctive practice of foraging wild resources and farming domesticated cultigens supported a sustained period of population growth from the San Pedro to the Cienega phase, and eventually probably led to a greater dependence on agricultural production during the Hohokam period, which further contributed to poor oral health.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, the fact that no significant differences were observed in the prevalence or frequency of caries or AMTL between temporal phases at La Playa suggests that dietary composition remained stable over the entire course of the Early Agricultural period. This is supported by the botanical evidence from sites in southern Arizona that demonstrate an overall increase in resource consumption, but not an increased reliance on domesticated cultigens (Adams, 1998;Schurr & Gregory, 2002). The conjunctive practice of foraging wild resources and farming domesticated cultigens supported a sustained period of population growth from the San Pedro to the Cienega phase, and eventually probably led to a greater dependence on agricultural production during the Hohokam period, which further contributed to poor oral health.…”
Section: Discussionsupporting
confidence: 48%
“…Schurr & Gregory (2002) identified a discrete example of this increase in local investment as a dramatic increase in maize ubiquity from storage features over a 200-year period during the middle part of the Cienega phase at Los Pozos. They also documented concomitant increases in the ubiquity of every other plant resource in these storage features, including seeds, grasses, cacti and mesquite: a trend mirrored by the increased presence of faunal remains, flaked stone and fire-cracked rock from middens (Schurr & Gregory, 2002). Adams (1998) found similar parallels in groundstone assemblages from Early Agricultural sites in the Tucson Basin.…”
Section: The Early Agricultural Periodmentioning
confidence: 99%
“…Although maize was introduced to this area from the south by ∼2100 B.C. (18,21,27), birth rates as proxied by 15 (19,28,29), the low juvenility indices reported here favor suggestions that these occupations tended to be short-lived (30,31) or part of a seasonal round (27), and perhaps most important, because this also affects mobility, focused on varieties of maize that were not yet very productive (32).…”
Section: Resultsmentioning
confidence: 88%
“…Schurr (1989) has demonstrated that fluoride dating can be successfully applied in studies of changes in health, diet, and mortuary practices over time before. Elsewhere he has demonstrated the utility of this method in seriating structures that are separated by relatively short occupation periods (Schurr and Gregory, 2002).…”
Section: The Burial Practices At Tell Halulamentioning
confidence: 99%